The Study on Socio-Economic Impacts of Tourism in the Golden Triangle of Odisha - MOHANTY, Rojalin; SAMAL, Ansuman (Theoretical and Practical Research in Economic Fields, 2023)
The Puri-Konark-Bhubaneswar “Golden Triangle” is not only Odisha's main draw but also has enormous potential as a tourist destination. Odisha, on India's eastern coast, is an auspicious Indian state with numerous opportunities and a wealth of sights to see. The state has many natural and cultural resources, such as its beaches, arts and crafts, temples and monuments, lakes, forests, and wildlife. Millions of worshippers from all over the world visit the temple of Lord Jagannath in Puribecause it is considered one of the holiest of holy dhams in India, alongside the Sun Temple at Konark, the sole World Heritage Monument in all of India. Bhubaneswar, the state capital, is home to a wide variety of well-known tourist attractions, such as the Lingaraj temple, the Rajarani temple “widely regarded as the crowning achievement of Kalingan architecture”, the Jain caves at Khandagiri and Udaygiri, the white tiger breeding grounds at Nandankanan, the site of the Kalingan war at Dhauligiri, and many others besides. Odisha has a lot of potential as a tourist destination, and there are many exciting things to see and do there, but the state has not seen a significant uptick in visitor numbers to match its product. This study mostly focused on a popular travel destination for the “Golden Triangle”. Many people travel to Puri each year to pay their respects to Lord Jagannath because it is considered to be one of the four Dhams. The group travels to Puri, the Sun Temple at Konark, and the Shiva Temple in Bhubaneswar. Since so many people flock to Odisha, the area around Bhubaneswar, Puri, and Konarkhas become known as the “Golden Triangle”.